2012
DOI: 10.1007/978-94-007-4719-7_7
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Determinants of Glioma Cell Invasion

Abstract: Tumor cell invasiveness is a critical challenge in the clinical management of glioma patients. In addition, there is accumulating evidence that current therapeutic modalities, including anti-angiogenic therapy and radiotherapy, can enhance glioma invasiveness. Glioma cell invasion is stimulated by both autocrine and paracrine factors that act on a large array of cell surface-bound receptors. Key signaling elements that mediate receptor-initiated signaling in the regulation of glioblastoma invasion are Rho fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 187 publications
1
57
0
1
Order By: Relevance
“…Glioblastoma invades surrounding tissue as single cells that often follow preferred anatomical routes including white matter tracts and the outside walls of blood vessels. Multiple studies have suggested a role for the Rac subclass of Rho GTPases in glioblastoma invasion [1][2][3] (reviewed in [4]). One limitation of these studies is that they were performed in glioblastoma cell lines that are not invasive in vivo in animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Glioblastoma invades surrounding tissue as single cells that often follow preferred anatomical routes including white matter tracts and the outside walls of blood vessels. Multiple studies have suggested a role for the Rac subclass of Rho GTPases in glioblastoma invasion [1][2][3] (reviewed in [4]). One limitation of these studies is that they were performed in glioblastoma cell lines that are not invasive in vivo in animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Cbl-mediated ubiquitylation and subsequent degradation of the α 5 and α 3 subunits may allow limiting of integrin-mediated signaling toward cell migration (Schaefer et al, 2012). There are several studies showing overexpression of integrin subunits in gliomas, correlating with increased invasion and migration both in vitro and in vivo (Kwiatkowska & Symons, 2013).…”
Section: Proteolytic Regulation Of Glioma Invasion Signalsmentioning
confidence: 99%
“…RhoA, Rac1 and Cdc 42 are the best characterized of the Rho GTPases and their expression, particularly Rac1, is consistently elevated in glioma tumors, correlating with high tumor grade and dismal prognosis (Kwiatkowska & Symons, 2013). Emerging evidence implicates the tumor suppressor HACE1, a HECTdomain containing E3 ubiquitin ligase, in the targeting of Rac1 to proteasome-mediated degradation (Torrino et al, 2011).…”
Section: Proteolytic Regulation Of Glioma Invasion Signalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Почти все сигнальные пути, принимающие участие в эмбриональном развитии, регуляции пролиферации и миграции, так или иначе, задействованы в глиомагенезе. Большое количество исследований посвящено проонкогенным свойствам таких путей, как PI3K (фосфоинозитид-3-киназа)/Akt (протеинкиназа, относящаяся к семейству протеинкиназ B), MAPK (митоген-активируемая протеинкиназа)/ERK (киназа, регулируемая внеклеточным сигналом), PLC (фосфолипаза C)/PKC (протеинкиназа C), WNT (комбинация Wingless (бескрылый) и Int), Notch1 (трансмембранный рецепторный белок человека), mTOR (mammalian target of rapamycin, серин-треониновая протеинкиназа) и некоторым другим [1]. Относительно недавно появились исследования, показывающие возможное вовлечение в онкогенез вообще и в глиомагенез в частности сигнального пути HH [2,3].…”
Section: Introductionunclassified